Method of applied information theory in estimating efficiency of structural organization of small group of aviation operators - Рева, О. М.; Борота, Н. В. (Proceedings of National Aviation University (archive), 1999)
Substantiated is the possibility of applying cybernetic methods of information chains for analysis of efficiency of structural organization of dispatcher team. To investigate it we have composed and solved a system of 10th order linear equation (used are direct current information chains ). It is proved that the general scheme must be decomposed, on the one hand, into a group of operative planning and management on the other hand. Worked out are the requirement to the group members